Menganalisis Permasalahan Komunikasi Anak Usia Dini 4-5 Tahun Di TK Asisi Medan - Maria Feronika Simatupang; Chamelia Tasri; Mei Febrina; Elya Siska Anggraini; Aman Simaremare (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Communication is a process where two or more people form or exchange information with each other. Communication is an important aspect in children's development, especially at the age of 4-5 years. At this age, children experience rapid development in their language and communication skills. However, some children may experience difficulties in communicating, which can hinder their social, emotional and academic development. This research uses a qualitative approach with observation methods with children. The research aims to analyze communication problems in children aged 4-5 years.